Mathematical Creative Thinking Ability Viewed by Adversity Quotient in Problem-Based Learning Integrated STEM (Unnes Journal of Mathematics Education, 2023)
The purposes of this study were (1) to know the average test results of students' mathematical creative thinking abilities with the Problem-Based Learning integrated STEM to achieve the standard of minimum completeness of mastery learning and classical mastery; (2) to find out students' creative thinking abilities with Problem-Based Learning integrated STEM is better than students' creative thinking abilities with Discovery Learning models; (3) to find out students' mathematical creative thinking ability increase in Problem-Based Learning integrated STEM; and (4) to determine and describe the effect of Adversity Quotient on students' mathematical creative thinking ability in the Problem-Based Learning integrated STEM. The method used was a mixed method with a sequential explanatory design. In this research, 6 research subjects were taken based on the level of Adversity Quotient in the experimental class. Research results show that (1) the average test results for students' mathematical creative thinking ability using the Problem-Based Learning integrated STEM achieved the standard of minimum completeness of mastery learning and classical mastery; (2) students' creative thinking abilities with the Problem-Based Learning integrated STEM are better than students' creative thinking abilities with Discovery Learning models; (3) there was an increase in students' mathematical creative thinking skills in the Problem-Based Learning integrated STEM model; (4) there is an influence of the Adversity Quotient on students' mathematical creative thinking abilities in the Problem-Based Learning integrated STEM; S-1, S-2, S-3, S-4, and S-5 are not yet able to fulfill the four indicators of mathematical creative thinking ability, and S-6 fulfills the four indicators of mathematical creative thinking ability